Velopharyngeal Configuration Changes following Le Fort I Osteotomy with Maxillary Advancement in Patients with Cleft Lip and Palate: A Cephalometric Study. (November 2015) - Wu, Yu; Wang, Xing; Ma, Lian; Li, Zili
Objective: To describe the morphological changes of velopharyngeal components in patients with cleft lip and palate after Le Fort I osteotomy with maxillary advancement and to clarify whether the velopharyngeal morphological changes are related to the distance of maxillary advancement. Design: Retrospective case series. Setting: Hospital and Stomatology Unit of Peking University, Beijing, China. Patients: A total of 47 patients with maxillary hypoplasia secondary to cleft lip and palate. Interventions: Le Fort I osteotomy combined with bilateral sagittal split ramus osteotomy and/or genioplasty for treatment of maxillofacial deformity. Main Outcome Measures: The lateral cephalometric radiographs with velum at rest (n = 47) and during phonation of /i/ (n = 17) were undertaken preoperatively (T1), 1 week postoperatively (T2), and at least 6 months postoperatively (T3). Some measure indices of velopharyngeal configuration were collected and analyzed. Results: The average maxillary advancement distance was 4.08 ± 1.58 mm. The velar length, velar angle, and nasopharyngeal depth increased, but velar thickness decreased. The motion of the soft palate had no significant change, but the motion of the posterior pharyngeal wall and the Passavant's ridge increased significantly. No significant linear correlation was found between maxillary advancement distance and velopharyngeal configuration changes. Conclusion: Correction of maxillary hypoplasia by Le Fort I osteotomy with maxillary advancement increases the velopharyngeal cavity depth, which may impair velopharyngeal competence. The compensatory effects of the velopharyngeal soft tissue and posterior pharyngeal wall may alleviate this impairment to a certain extent.